The developmental changes of fecal microbial composition and diversity in emu (Dromaius novaehallandiae) at early growth stages - Deng, Leru; Chen, Xinyi; Pan, Shuhan; Huang, Wenling; Yin, Yucheng; Wei, Xueyan; Zhang, Huihua; Zhu, Cui (Frontiers in Microbiology, 2026)
The early postnatal period plays a crucial role in the establishment and maturation of the gut microbiome in avian hosts, significantly influencing their metabolic processes and overall health. This study was carried out to characterize the ontogenetic development of fecal microbiota in emus (Dromaius novaehollandiae) during critical early growth stages from days 7 to 28 post-hatch using 16S rRNA gene sequencing. The results indicated that rank abundance and rarefaction curves confirmed adequate sequencing depth for capturing microbial diversity across all age groups. The dominant phyla of fecal microbiota in emus included Firmicutes, Proteobacteria, and Bacteroidetes, with successional shifts observed at order, family, and genus levels. As emus advanced in age, fecal microbiota underwent significant changes in microbial community, diversity, and function. The α-diversity indices (Observed species, Shannon, PD whole tree, Chao1, and ACE) in the feces of emus peaked significantly at d 21 (p < 0.05). The β-diversity analysis revealed significant structural differences in microbial communities between different ages, particularly between d14 and d7, d21 vs. d7, and d14 vs. d28 (p < 0.05). Linear discriminant analysis Effect Size (LEfSe) identified 26 discriminative biomarkers with stage-specific enrichments, including Turicibacter (d7/d28), Erysipelotrichaceae (d7/d14), Bacteroidetes (d21), and Corynebacteriaceae as well as Actinobacteria (d28). T-test validation confirmed significant temporal variations in phylum (Firmicutes, Actinobacteria, and Bacteroidetes) and genus-level abundances (e.g., Bacteroides and Lactobacillus) in the feces of emus (p < 0.05). PICRUSt functional prediction indicated age-dependent metabolic pathway enrichment, including amino and nucleotide sugar metabolism (d7), oxidative phosphorylation (d14), ABC transporters and cysteine metabolism (d21), and genetic information processing pathways (d28). These results demonstrated dynamic, stage-specific restructuring of the fecal microbiota and its metabolic potential during early development in emus. This research presented the initial longitudinal assessment of fecal microbiota development in emus throughout their crucial early developmental stage, revealing age-dependent alterations in microbial composition and metabolic activity that could guide enhanced nutritional and health approaches for ratites.